Verbal fluency and risk of dementia. (21st March 2019) - Sutin, Angelina R.; Stephan, Yannick; Terracciano, Antonio
Abstract : Objective: Verbal fluency is a common neuropsychological test that is impaired in dementia. We test whether verbal fluency is a prospective risk factor for incident dementia, cognitive impairment not dementia (CIND), and conversion from CIND to dementia. Methods: Participants (N = 18 189) from the Health and Retirement Study were administered a standard test of verbal fluency and were assessed for cognitive status every 2 years between baseline and 6 years' follow‐up. Results: Every standard deviation increase in verbal fluency was associated with an approximately 60% reduced risk of incident dementia, an approximately 25% reduced risk of incident CIND, and an approximately 25% reduced risk of conversion from CIND to dementia. These associations were independent of age, gender, education, race, ethnicity, and APOE risk status. The associations were slightly weaker (but still significant) for African Americans and individuals with lower education. There was no interaction between verbal fluency and APOE risk status. Conclusion: Verbal fluency is an easily administered task that is predictive of incident cognitive impairment.